Calcium catalyzed enantioselective intramolecular alkene hydroamination with chiralC2-symmetric bis-amide ligands - Stegner, Philipp; Eyselein, Jonathan; Ballmann, Gerd; Langer, Jens; Schmidt, Jochen; Harder, Sjoerd (Dalton Transactions, 2021)
The chiral building block (R)-(+)-2,2′-diamino-1,1′-binaphthyl, (R)-BINAM, which is often used as backbone in privileged enantioselective catalysts, was converted to a series ofN-substituted proligandsR1-H2(R = CH2tBu, C(H)Ph2, PPh2, dibenzosuberane, 8-quinoline). After double deprotonation with strong Mg or Ca bases, a series of alkaline earth (Ae) metal catalystsR1-Ae·(THF)nwas obtained. Crystal structures of theseC2-symmetric catalysts have been analyzed by quadrant models which show that the ligands with C(H)Ph2, dibenzosuberane and 8-quinoline substituents should give the best steric discrimination for the enantioselective intramolecular alkene hydroamination (IAH) of the aminoalkenes H2C=CHCH2CR′2CH2NH2(CR′2= CPh2, CCy or CMe2). The dianionicR12−ligand inR1-Ae·(THF)nfunctions as reagent that deprotonates the aminoalkene substrate, while the monoanionic (R1-H)−ligand formed in this reaction functions as a chiral spectator ligand that controls the enantioselectivity of the ring closure reaction. Depending on the substituent R in the BINAM ligand, full cyclization of aminoalkenes to chiral pyrrolidine products as fast as 5 minutes was observed. Product analysis furnished enantioselectivities up to 57% ee, which marks the highest enantioselectivity reported for Ca catalyzed IAH. Higher selectivities are impeded by double protonation of theR12−ligand leading to complete loss of chiral information in the catalytically active species.
CRIS-Team Scopus Importer:2021-03-19

d–d Dative Bonding Between Iron and the Alkaline-Earth Metals Calcium, Strontium, and Barium - Stegner, Philipp; Färber, Christian; Oetzel, Jan; Siemeling, Ulrich; Wiesinger, Michael; Langer, Jens; Pan, Sudip; Holzmann, Nicole; Frenking, Gernot; Albold, Uta; Sarkar, Biprajit; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Double deprotonation of the diamine 1,1′-(tBuCH2NH)-ferrocene (1-H2) by alkaline-earth (Ae) or EuII metal reagents gave the complexes 1-Ae (Ae=Mg, Ca, Sr, Ba) and 1-Eu. 1-Mg crystallized as a monomer while the heavier complexes crystallized as dimers. The Fe⋅⋅⋅Mg distance in 1-Mg is too long for a bonding interaction, but short Fe⋅⋅⋅Ae distances in 1-Ca, 1-Sr, and 1-Ba clearly support intramolecular Fe⋅⋅⋅Ae bonding. Further evidence for interactions is provided by a tilting of the Cp rings and the related 1H NMR chemical-shift difference between the Cp α and β protons. While electrochemical studies are complicated by complex decomposition, UV/Vis spectral features of the complexes support Fe→Ae dative bonding. A comprehensive bonding analysis of all 1-Ae complexes shows that the heavier species 1-Ca, 1-Sr, and 1-Ba possess genuine Fe→Ae bonds which involve vacant d-orbitals of the alkaline-earth atoms and partially filled d-orbitals on Fe. In 1-Mg, a weak Fe→Mg donation into vacant p-orbitals of the Mg atom is observed.
CRIS-Team Scopus Importer:2020-07-10
Keywords: alkaline-earth metals; ferrocene; metal–metal bonding; theoretical chemistry

Enantioselective Catalysis with s-Block Organometallics - Stegner, Philipp; Harder, Sjoerd (Early Main Group Metal Catalysis: Concepts and Reactions, 2019)
Although enantioselective catalysis is a major technology within the larger field of transition metal catalysis, s-block metal-based chiral catalysts are much less explored. Because the pharmaceutical industry is interested in the synthesis of enantiopure chiral building blocks and simultaneously aims to find benign substitutes for Pt catalysts, further development of organic key transformations mediated by chiral early main group metal catalysts is rewarding. This chapter summarizes research activities in this field and describes the breakthroughs and pitfalls that form the basis for future research.<br
CRIS-Team WoS Importer:2021-08-13
Keywords: Alkali metals; Alkaline earth metals; Catalysis; Chiral; Enantioselective

Intramolecular Alkene Hydroamination with Hybrid Catalysts Consisting of a Metal Salt and a Neutral Organic Base - Stegner, Philipp; Fischer, Christian; Nguyen, D. Thao; Rösch, Andreas; Penafiel, Johanne; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2020)
Hybrid catalysts consisting of alkaline earth iodides (AeI2) and the Schwesinger base tBuP4 catalyse the intramolecular alkene hydroamination of H2C=CHCH2CR2CH2NH2 [CR2=CPh2, C(CH2)5, CMe2]. Activities decrease along the row: Ca > Sr >> Mg > Ba. Hybrid catalysts consisting of tBuP4 and ZnI2, AlI3, FeCI3 or NaI were found to be fully inactive. Also, the hybrid catalyst tBuP3/CaI2 was not active which means that the base strength of the non-nucleophilic organic base must be higher than that of tBuP3 (pKa BH+ = 38.6). Combinations of tBuP4 with CaX2 (X = Cl, Br, OiPr, OTf, NTf2) were found to be fully inactive which may in part be explained by poor solubility. The hybrid catalysis method is therefore limited to the combination tBuP4/CaI2 but the iodide ligands may be partially or fully replaced by chiral ligands. Chiral modifications of the hybrid catalysts gave in intramolecular alkene hydroamination ee values up to 33 %.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Calcium; Homogeneous catalysis; Intramolecular alkene hydroamination; Schwesinger bases

Metallic Barium: A Versatile and Efficient Hydrogenation Catalyst - Stegner, Philipp; Färber, Christian; Zenneck, Ulrich; Knüpfer, Christian; Eyselein, Jonathan; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Ba metal was activated by evaporation and cocondensation with heptane. This black powder is a highly active hydrogenation catalyst for the reduction of a variety of unactivated (non-conjugated) mono-, di- and tri-substituted alkenes, tetraphenylethylene, benzene, a number of polycyclic aromatic hydrocarbons, aldimines, ketimines and various pyridines. The performance of metallic Ba in hydrogenation catalysis tops that of the hitherto most active molecular group 2 metal catalysts. Depending on the substrate, two different catalytic cycles are proposed. A: a classical metal hydride cycle and B: the Ba metal cycle. The latter is proposed for substrates that are easily reduced by Ba0, that is, conjugated alkenes, alkynes, annulated rings, imines and pyridines. In addition, a mechanism in which Ba0 and BaH2 are both essential is discussed. DFT calculations on benzene hydrogenation with a simple model system (Ba/BaH2) confirm that the presence of metallic Ba has an accelerating effect.
CRIS-Team Scopus Importer:2020-12-25
Keywords: alkaline earth metals; barium; hydride; hydrogenation catalysis; metal activation

Strontium Chemistry with Silicone Grease - Harder, Sjoerd; Freitag, Benjamin; Stegner, Philipp; Pahl, Jürgen; Naglav, Dominik (Zeitschrift für Anorganische und Allgemeine Chemie, 2015)
Reaction of Sr(2-Me2N–Me3Si-benzyl)(2)(THF)(2) with one equivalent of DIPP(H)N-BH-N(H)DIPP (NBN-H-2, DIPP = 2,6-iPr-phenyl) gave the strontium bora-amidinate complex Sr(NBN)(THF)(4). Traces of silicone grease, however, can change the course of the reaction completely and gave the product Sr[(DIPP)NSiMe2O]THF(4) (1) in a ca. 25% yield. Complex 1 is a S-4 symmetric cluster with a Sr4O4 core and four chelating amide side arms. From the mother liquor a second product could be isolated: the dimeric cluster [Sr(NBN-SiMe2OSiMe2O)THF](2) (2). Whereas the synthesis of complex 2 is not reproducible, complex 1 can be prepared by deliberate addition of silicone grease. Also, it was found that Sr[N(SiMe3)(2)](2), 2,6-diisopropylphenyl and cyclic hexamethyltrisiloxane can be used as the reagents. For reactions with silicone grease, a mechanism, in which silicone precoordinates the central Sr atom followed by nucleophilic Si-O bond fission is proposed.
Keywords: Amides; Strontium; Silicone

Teaming up main group metals with metallic iron to boost hydrogenation catalysis - Färber, Christian; Stegner, Philipp; Zenneck, Ulrich; Knüpfer, Christian; Bendt, Georg; Schulz, Stephan; Harder, Sjoerd (Nature Communications, 2022)
Hydrogenation of unsaturated bonds is a key step in both the fine and petrochemical industries. Homogeneous and heterogeneous catalysts are historically based on noble group 9 and 10 metals. Increasing awareness of sustainability drives the replacement of costly, and often harmful, precious metals by abundant 3d-metals or even main group metals. Although not as efficient as noble transition metals, metallic barium was recently found to be a versatile hydrogenation catalyst. Here we show that addition of finely divided Fe-0, which itself is a poor hydrogenation catalyst, boosts activities of Ba-0 by several orders of magnitude, enabling rapid hydrogenation of alkynes, imines, challenging multi-substituted alkenes and non-activated arenes. Metallic Fe-0 also boosts the activity of soluble early main group metal hydride catalysts, or precursors thereto. This synergy originates from cooperativity between a homogeneous, highly reactive, polar main group metal hydride complex and a heterogeneous Fe-0 surface that is responsible for substrate activation.
CRIS-Team WoS Importer:2022-07-01

Transmetalation from Magnesium–NHCs—Convenient Synthesis of Chelating π-Acidic NHC Complexes - Messelberger, Julian; Grünwald, Annette; Stegner, Philipp; Senft, Laura; Heinemann, Frank Wilhelm; Munz, Dominik (Inorganics, 2019)
The synthesis of chelating N-heterocyclic carbene (NHC) complexes with considerable -acceptor properties can be a challenging task. This is due to the dimerization of free carbene ligands, the moisture sensitivity of reaction intermediates or reagents, and challenges associated with the workup procedure. Herein, we report a general route using transmetalation from magnesium-NHCs. Notably, this route gives access to transition-metal complexes in quantitative conversion without the formation of byproducts. It therefore produces transition-metal complexes outperforming the conventional routes based on free or lithium-coordinated carbene, silver complexes, or in situ metalation in dimethyl sulfoxide (DMSO). We therefore propose transmetalation from magnesium-NHCs as a convenient and general route to obtain NHC complexes.
CRIS-Team WoS Importer:2019-06-28